Pledge for a transformative science: A conceptual framework - Uwe Schneidewind; Mandy Singer-Brodowski; Karoline Augenstein; Franziska Stelzer (Wuppertal Institut für Klima, Umwelt, Energie, 2016)
"Transformative science" is a concept that delineates the new role of science for knowledge societies in the age of reflexive modernity. The paper develops the program of a transformative science, which goes beyond observing and analyzing societal transformations, but rather takes an active role in initiating and catalyzing change processes. The aim of transformative science is to achieve a deeper understanding of ongoing transformations and increased societal capacity for reflexivity with regard to these fundamental change processes. The concept of transformative science is grounded in an experimental paradigm, which has implications for (1) research, (2) education and learning, and (3) institutional structures and change in the science system. The article develops the theoretical foundations of the concept of transformative science and spells out the concrete implications in these three dimensions. – – Das Konzept einer "Transformative Wissenschaft" bietet Antworten auf die neue Rolle von Wissenschaft in den Wissensgesellschaften der "Reflexiven Moderne". Das Paper entfaltet das Programm einer "Transformativen Wissenschaft", die gesellschaftliche Transformationsprozesse nicht nur beobachtet und von außen beschreibt, sondern diese Veränderungsprozesse selber mit anstößt und katalysiert. Transformative Wissenschaft zielt dabei auf ein verbessertes Verständnis und eine umfassende gesellschaftliche Reflexion dieser Veränderungsprozesse. Sie folgt einem experimentellen Paradigma und wirkt sowohl auf die (1) Forschungs-, die (2) Lern- und Lehrprozesse als auch auf (3) die institutionelle Weiterentwicklung im Wissenschaftssystems zurück. Das Paper gibt einen Einblick in die Hintergründe und in die Implikationen in allen drei Dimensionen.
urn:nbn:de:bsz:wup4-opus-64142
Keywords: 330